Estimation of Eigenvalues for the ψ-Laplace Operator on Bi-Slant Submanifolds of Sasakian Space Forms - Alkhaldi, Ali H.; Khan, Meraj Ali; Aquib, Mohd.; Alqahtani, Lamia Saeed (Frontiers in Physics, 2022)
This study attempts to establish new upper bounds on the mean curvature and constant sectional curvature of the first positive eigenvalue of the ψ-Laplacian operator on Riemannian manifolds. Various approaches are being used to find the first eigenvalue for the ψ- Laplacian operator on closed oriented bi-slant submanifolds in a Sasakian space form. We extend different Reilly-like inequalities to the ψ-Laplacian on bi-slant submanifolds in a unit sphere depending on our results for the Laplacian. The conclusion of this study considers some special cases as well.